1988
DOI: 10.1227/00006123-198806010-00028
|View full text |Cite
|
Sign up to set email alerts
|

Teflon Injection for Vocal Cord Paralys is after Intracranial Operation

Abstract: Vocal cord paralysis may follow intracranial operation if the vagus nerve is damaged intraoperatively. If the resulting laryngeal incompetence is severe, hoarseness, dysphagia, and aspiration may develop. This is often followed by a pneumonitis requiring chronic gastric tube feeding. Teflon vocal cord injection has been shown to restore the sphincteric action of the larynx and enable patients to phonate and swallow properly again. Nine patients underwent this procedure for chronic aspiration and hoarseness. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In 1998, Heller et al. 18 reported that an intracordal Teflon injection appeared to relieve aspiration for high vagal paralysis following intracranial surgery. However, Teflon injections, complicated with foreign body inflammation and granuloma, have not often been performed in recent years 19 .…”
Section: Discussionmentioning
confidence: 99%
“…In 1998, Heller et al. 18 reported that an intracordal Teflon injection appeared to relieve aspiration for high vagal paralysis following intracranial surgery. However, Teflon injections, complicated with foreign body inflammation and granuloma, have not often been performed in recent years 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies of LF procedures cited rates of diet liberation ranging from 69% to 75%, 19,22 while studies of IL had rates ranging from 70% to 100%. 34,36,37,40,41 Patient-reported dysphagia outcome measures were more variable for LF and IL. In studies that attempted to compare outcomes between LF and IL procedures, 12,23,43 there were in general no significant differences in outcomes shortly following surgery.…”
Section: Qualitative Analysismentioning
confidence: 99%
“…Thirteen studies had sufficient data to be in the quantitative analysis of complications. 14,17,20,23,25,[31][32][33][34][35][36][37][38] The overall estimated complication rate (major and minor) was 10% (95% CI, 6%,14%). When stratified by procedure, the pooled estimated complication rate (major and minor) was 7% (95% CI, 2%-13%) for IL (Figure 2) and 15% (95% CI, 10%-20%) for LF surgery (Figure 3).…”
Section: Quantitative Analysis Of Complicationsmentioning
confidence: 99%
See 2 more Smart Citations